2016
DOI: 10.4209/aaqr.2015.04.0237
|View full text |Cite
|
Sign up to set email alerts
|

Residential Biomass Burning Emissions over Northwestern Himalayan Region of India: Chemical Characterization and Budget Estimation

Abstract: In the present study, we have determined the emission factors (EF) and estimated the emission of particulate matter (PM), organic carbon (OC), elemental carbon (EC), polycyclic aromatic hydrocarbons (PAHs), water soluble inorganic constituents (WSIC) and trace gases such as SO 2 , NO and NO 2 from the combustion of biomass fuels (FW: fuel wood and DC: dung cake) used in rural sectors for cooking over Himachal Pradesh (HP), representing the Northwestern Himalayan region of India. The average EFs of PM estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Therefore, apart from forest fire burning emissions, fuelwood can also influence the air quality in the surrounding region. An earlier study revealed that the PM estimate from biomass fuel is about 8.61 ± 4.54 Gg/ year, which is higher than several north Indian states [55].…”
Section: Influence Of Biomass/fuel Wood Burning On Air Qualitymentioning
confidence: 78%
“…Therefore, apart from forest fire burning emissions, fuelwood can also influence the air quality in the surrounding region. An earlier study revealed that the PM estimate from biomass fuel is about 8.61 ± 4.54 Gg/ year, which is higher than several north Indian states [55].…”
Section: Influence Of Biomass/fuel Wood Burning On Air Qualitymentioning
confidence: 78%
“…The EC concentrations are higher in evening time than in the morning time as wood was being used in the evening time for heating purposes and dung cake in the morning for cooking. 50 Clearly, in afternoon times when cooking is not taking place, concentrations of OC and EC in Budhwada (M.P.) was decreased only by 44.6% and 33.8% respectively whereas in Baggi (H.P.)…”
Section: Results and Discussion Variation Of Ec And Oc In Households Time-wise Variationmentioning
confidence: 93%
“…The moisture content in fuelwood is lesser as compared to dung cake, hence fuelwood contributes higher emissions of EC. 50,54 biomass burning was least in this house and so are the emissions. Among all the houses, house H had the average concentrations of OC and EC at 92.56 ± 47.14 µg/m 3 and 54.93 ± 24.72 µg/m 3 respectively.…”
Section: Results and Discussion Variation Of Ec And Oc In Households Time-wise Variationmentioning
confidence: 96%
“…Direct aerosol measurements studies over the western and northwestern Himalaya hill stations also supports a predominant burnt carbon biomass source. 53,54 Given that it is well known that OC ff particles are more readily transported over longdistances compared to OC bio 55 , and thus, if OC bio were transported from geographically distant sources, OC ff particles were expected to be similar or higher in concentration compared to OC bio in western Himalayan glaciers. The near absence of OC ff and prevalence of local air mass circulation therefore indicate that carbonaceous particles in western Himalaya are only derived from locally burnt biomass sources.…”
Section: Resultsmentioning
confidence: 99%